Arabic Video Lyric Untuk Meningkatkan Pemahaman Kosakata Bahasa Arab Siswa - Kudsiyah Kudsiyah; Lailatul Mauludiyah; Murdiono Murdiono (UIN Sunan Gunung Djati Bandung, 2021)
Video song media was a medium that presents material in the form of text and images as well as monologue sound about the material so that students can watch and listen to videos in the learning process. The purpose of this study was to determine the effectiveness of the video song media in increasing understanding of Arabic vocabulary. This research was a quantitative research. This research was conducted at SD Muahmmadiyah 8 KH Mas Mansur Malang. The subjects taken from this study were the VA class, which amounted to 25 students from a population of 79 students using purposive sampling technique. In this study, data collection techniques were carried out in the form of interviews, questionnaires, tests and documentation. The instrument used in the interview is the interview sheet, while the questionnaire instrument sheet is a questionnaire sheet consisting of several questions related to the video song media, the instrument sheet used in the test is a test question in the form of an interactive online game, the tests used are pretest and posttest. To find out the results of the data in this study the researcher used the T test for the related sample, while to determine the effectiveness of the video media, the researcher used the N-gain formula. The collected research data is presented with descriptive statistics in the calculation of processing using SPSS 20. As for the results and testing of the hypothesis,